2004
DOI: 10.1111/j.1365-2265.2004.02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of nonalcoholic hepatic steatosis to overnight low‐dose dexamethasone suppression test in obese individuals

Abstract: These results suggest that nonalcoholic hepatic steatosis is closely correlated with a subtle, chronic activation of the HPA axis in obese, otherwise healthy, individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…Previously it has been shown that obese individuals [12] and overweight people with type 2 diabetes [31] with fatty liver have higher 24-h urinary free cortisol excretion with impaired dexamethasone suppression of cortisol compared with control subjects. However, the effect of fatty liver per se on cortisol metabolism is not differentiated from the effect mediated by obesity in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it has been shown that obese individuals [12] and overweight people with type 2 diabetes [31] with fatty liver have higher 24-h urinary free cortisol excretion with impaired dexamethasone suppression of cortisol compared with control subjects. However, the effect of fatty liver per se on cortisol metabolism is not differentiated from the effect mediated by obesity in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is uncertain whether abnormal cortisol regulation or metabolism is responsible for the marked insulin resistance. To date, abnormalities of cortisol regulation have been described in NAFLD, including chronic activation of the HPA axis [12][13][14][15], increased urinary excretion of cortisol, and impaired suppression of cortisol [14]. However, whether these abnormalities occur because of insulin resistance, liver fat per se, or because of the association of increased body fat with NAFLD is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of 5beta-reductase in men may contribute to altered bile acid and cholesterol metabolism in NASH. NAFLD is closely correlated with a subtle, chronic activation of the HPA axis in obese, otherwise healthy, individuals [41]. A weaker point of this study, though, is the absence of any histological liver data.…”
Section: Cortexmentioning
confidence: 96%
“…Much has been learned about glucocorticoid action from these excess states, and they can inform about the role 11␤-HSD1 may play in driving tissue-specific glucocorticoid excess in more common and diverse disease processes. Patients with nonalcoholic fatty liver disease (NAFLD), which is often associated with obesity and type 2 diabetes, have increased cortisol metabolite excretion (77)(78)(79) and decreased suppression by dexamethasone, independent of confounding factors such as body mass index (BMI) and insulin resistance (79,80), with the degree of HPA activation positively correlated with the severity of liver histopathology (79).…”
Section: A Hpa Axis In Metabolic Diseasementioning
confidence: 99%